Giving back Filipino America and the politics of diaspora giving - Mariano, L. Joyce Zapanta 1973- (Philadelphia Temple University Press, 2021)
"Examines Filipino diaspora through the complex of meanings associated with "giving back" and explores the process of diaspora formation. Argues that giving-related institutions and discourse-such as aid, development, altruism, and benevolence-are integral to understanding diaspora formation today"--
Introduction: "Charity Begins at Home" -- Good Diasporic Returns: Immigrant Philanthropy, Overseas Labor Remittances, and the American Dream -- Homeland Disorientations: Toward Antidevelopmentalist Diaspora-Giving Politics -- Incorporating Dreams: Discourses of Poverty and Responsibility in Diaspora -- Philippine Environments and Critical Ecologies of Diaspora Giving -- Epilogue: Diasporic Love.
Includes bibliographical references and index.
Keywords: Filipino diaspora; Charities -- Philippines; Emigrant remittances -- Philippines; Filipino Americans -- Charitable contributions; Filipinos -- United States -- Social conditions